Programmable design of synthetic plant immune receptors for pathogen protein recognition - Haocheng Zhu; Dandan Jiang; Qiao Zhang; Kang Zhang; Kevin Tianmeng Zhao; Jin-Long Qiu; Caixia Gao (Science, 2026)
The limited diversity and recognition scope of natural plant immune receptors impede resistance breeding against rapidly evolving pathogens. Here we report programmable design of synthetic plant immune receptors (SPIRs). De novo designed binding modules targeting pathogen proteins were grafted into the integrated decoy (ID) domain of a plant immune receptor. SPIRs recognized proteins derived from viral, bacterial, fungal, and oomycete pathogens. Their performance was improved by combining AI-guided protein design with in planta directed evolution, enhancing immune activation while reducing autoactivation. SPIRs exhibited high target specificity and could be stacked for multiplexed recognition of pathogen proteins. Importantly, viral-targeting SPIRs responded to infectious clones of plant viruses, and transgenic plants expressing SPIRs conferred disease resistance. This work establishes a versatile platform for efficient plant immunity engineering.